Socio-demographic, psychosocial and environmental factors associated with suicidal behaviour in Indigenous Sami and Greenlandic Inuit adolescents; the WBYG and NAAHS studies - Granheim, Ida Pauline Høilo; Silviken, Anne; Larsen, Christina Viskum Lytken; Kvernmo, Siv (International Journal of Circumpolar Health, 2021)
Background - For young Indigenous people, suicide is one of the leading causes of death, and high rates in Arctic areas indicate serious health- and societal concerns. More knowledge is needed, as suicidal behaviour predictslater death by suicide. Objectives - The objective was to study associations between suicidal thoughts and suicide attempts and socio-demographic, psychosocial, and environmental factors in Sami and Greenlandic adolescents, within and between groups and gender. Methods - Working samples included 442 Sami and 399 Greenlandic Inuit (15-16-year-olds), in “The Norwegian Arctic Adolescent Health Study” (NAAHS) and “Well–being among Youth in Greenland” (WBYG). Multivariable logistic regression explored associations between suicidal behaviour and family , ethnic language , school, friendship, and suicide in close relations. Results - Across Indigenous groups, suicidal behaviour was associated with the female gender, relationships with parents, suicide of friends, and rural living. Sami adolescents in stepparent families reported more suicidal behaviour. Inuit adolescents living outside the family and with poor school performance reported more suicidal thoughts. Inuit adolescents spending less time with friends reported more attempts. Gender differences occurred in both groups. Conclusion - To Sami and Greenlandic Inuit, family and peer relations are important factors of suicidal behaviour. Prevention programmes should be sensitive to gender and bereavement.